AFP mRNA level in enriched circulating tumor cells from hepatocellular carcinoma patient blood samples is a pivotal predictive marker for metastasis. Issue 1 (1st August 2016) - Jin, Junhua; Niu, Xiaojuan; Zou, Lihui; Li, Lin; Li, Shugang; Han, Jingli; Zhang, Peiying; Song, Jinghai; Xiao, Fei
Highlights: Circulating tumor cells from hepatocellular carcinoma blood samples are enriched with anti-EpCAM nanoparticles. Patients maintaining with positive AFP mRNA expression in CTCs are diagnosed as metastasis. Positive AFP mRNA of CTCs might be a pivotal predictor for HCC metastasis before and after hepatectomy. Abstract: Circulating tumor cells (CTCs) quantification may be helpful for evaluating cancer dissemination, predicting prognosis and assessing therapeutic effectiveness and safety. In the present study, CTCs from blood samples of 72 patients with hepatocellular carcinoma (HCC) were enriched with anti-EpCAM nanoparticles. AFP mRNA level was detected by nested polymerase chain reaction (PCR) after enrichment of CTCs from HCC blood samples at 0, 3, 6, 9 and 12 months after hepatectomy, respectively. AFP mRNA expression in CTCs was positive in 43 patients (59.7%) and negative in 29 patients (40.3%) before hepatectomy. Among 43 patients with positive AFP mRNA expression in CTCs before hepatectomy, 10 and 11 were diagnosed as intrahepatic/extrahepatic metastasis before and after hepatectomy, respectively. In addition, these 21 patients with metastasis had persisting positive AFP mRNA of CTCs during the whole tested year. Specifically, 3 patients with AFP mRNA negative in CTCs before hepatectomy changed to be positive at 6 and 9 months, and 2 of them were diagnosed as metastasis 12 months after hepatectomy. We conclude that the positive AFP mRNA of CTCs can be a pivotal predictor for HCC metastasis before and after hepatectomy. The release of AFP expression from hepatocellular carcinoma cells into circulation must be a major source of HCC metastasis.